AR, VR, and the Metaverse in Teaching: An Advocacy for Precise Differentiation - Thiele, Günther; Mirica, Katherine A.; Lau, Kah Chun; Habig, Sebastian (Journal of Chemical Education, 2023)
Augmented reality, virtual reality, mixed reality, and extended reality are becoming prominent in science education. However, in many reports on the matter, there is no clear differentiation between these different technologies. We comment on potential distinctions to avoid confusion and recommend a clear separation and naming of technology, as well as interactive and immersive level.<br
Keywords: Augmented Reality; Virtual Reality; Mixed Reality; Extended Reality; Nomenclature